The Effect Ofhypnobirt Hing On The Intensity Of Pain In Childbirth Penuunan Kala 1 In Midwives Clinic Nining - Lili Yuliana Tambunan; Maidina Putri; Widya Surya Tri Pasa; Paramita Mustari; Sri Junita Simaremare (Jurnal EduHealth, 2023)
Discussion:Hypnobirthing is a technique that helps pregnant women get positive suggestions during pregnancy until before delivery so that pregnant women can undergo a smooth, safe and comfortable delivery process. One of the non-pharmacological methods that can be used to reduce labor pain is hypnobirthing. Objective: The purpose of this study was to determine the effect of hypnobirthing relaxation techniques to reduce pain in the first stage of midwifery clinic Nining. Method: this type of research is “Quasi experimental prepost test " which provides treatment or intervention on the subject of research and then the impact of the treatment is measured and analyzed. The population in this study is all mothers who came to the clinic midwives first time Nining at the time of the study was conducted with a sample of 20 people by way of purposive sampling. This research was conducted on June 2 Junito 2 Juli 2023 with the observation sheet measurement method. Data processing was done using the wilcoxon test. Results: the results of univariate analysis obtained that the majority of labor pain before being given hypnobirthing relaxation techniques are in the category of moderate pain by 57.2% and the majority hypnobirthingof labor pain after being given hypnobirthing relaxation techniques are in the category of mild pain by 68.6% while the results of bivariate analysis obtained that there is no effect of hypnobirthing value p value 0.000 <③: 0.05. Conclusion: expected to health workers in order to improve health promotion of maternity about the benefits of relaxation techniques hypnobirthing during childbirth.